On the space-time admitting some geometric structures on energy-momentum tensors (2017)
This paper presents a study of a general relativistic perfect fluid space-time admitting various types of curvature restrictions on energy-momentum tensors and brings out the conditions for which uids of the space-time are sometimes phantom barrier and some other times quintessence barrier. The existence of a space{time where fluids behave as phantom barrier is ensured by an example.